2017
DOI: 10.1159/000479399
|View full text |Cite
|
Sign up to set email alerts
|

Hydralazine is a Suitable Mimetic Agent of Hypoxia to Study the Impact of Hypoxic Stress on In Vitro Blood-Brain Barrier Model

Abstract: Background/Aims: Understanding cellular mechanisms induced by hypoxia is fundamental to reduce blood-brain barrier (BBB) disruption. Nevertheless, the investigation of hypoxia on cellular pathways is complex with true hypoxia because HIF-1α has a short lifetime and rapidly reverts back to a normoxic state. To overcome this difficulty, mimetic agents of the hypoxia pathway have been developed, including the gold standard CoCl2. In this study, we proposed to compare CoCl2 and hydralazine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…We assessed if conjugation of peptides enhances the ability of TN-APNPs to penetrate the compromised BBB by using an in vitro BBB model, which was established by culturing hCMEC/D3 cells on the top and astrocyte NHA cells at the bottom of the insert membrane (Figure 2D). Disruption of the BBB was induced by adding CoCl 2 as previously reported21 and confirmed by quantification of transepithelial/transendothelial electrical resistance (TEER) values (Figure 2E). We found that all NPs, including TN-APNPs, C-TN-APNPs, and CC-TN-APNPs, demonstrated a high degree of BBB permeability, which is significantly greater than that of free Tat-NR2B9c peptide (Figure 2F).…”
Section: Resultssupporting
confidence: 86%
“…We assessed if conjugation of peptides enhances the ability of TN-APNPs to penetrate the compromised BBB by using an in vitro BBB model, which was established by culturing hCMEC/D3 cells on the top and astrocyte NHA cells at the bottom of the insert membrane (Figure 2D). Disruption of the BBB was induced by adding CoCl 2 as previously reported21 and confirmed by quantification of transepithelial/transendothelial electrical resistance (TEER) values (Figure 2E). We found that all NPs, including TN-APNPs, C-TN-APNPs, and CC-TN-APNPs, demonstrated a high degree of BBB permeability, which is significantly greater than that of free Tat-NR2B9c peptide (Figure 2F).…”
Section: Resultssupporting
confidence: 86%
“…Our decision to exploit a triple-culture model rather than a single endothelial cell layer system was driven by the need to generate a system capable of mimicking as faithfully as possible the in vivo BBB environment; in fact, it has been widely demonstrated how the direct coculture of BBB cellular components, like astrocytes alongside with brain endothelial cells, is able to enhance both TEER values and expression of specific proteins like the P-glycoprotein (P-gp), granting a more restrictive and physiologically relevant model through a significant reduction in paracellular transport of model compounds in comparison with monoculture and with indirect coculture . The TEER values reported at the fifth day of culture for our system (TEER = 70 Ω·cm 2 ) are comparable with the results described in the literature obtained with the same endothelial cell line, being higher than reported values for single bEnd.3 cultures (around 30 Ω·cm 2 ), and similar to other coculture systems like bend.3/C6 (TEER = 80 Ω·cm 2 ). Moreover, we were able to demonstrate through confocal microscopy analysis the expression of the ZO-1 protein by bEnd.3 cells (Figure b), specifically localized in the cell-to-cell contact regions, suggesting the formation of tight junction structures .…”
Section: Resultsmentioning
confidence: 99%
“…We also observed an upregulation in P-gp protein expression and functionality and a downregulation in BCRP [ 35 , 36 , 37 ]. We could not exclude that an adaptative mechanism exists to avoid BBB breakdown linked to other mechanisms involving other proteins like ABC channel membrane transporters, as observed in our in vitro studies [ 35 ].…”
Section: Discussionmentioning
confidence: 99%